2022
DOI: 10.3390/cancers14174149
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Prostate Cancer Survival

Abstract: It is not clear to what extent the age of diagnosis and the attained age impact on cancer mortality rates in men with newly diagnosed prostate cancer. We estimated annual prostate cancer mortality rates and 20-year survival rates according to the age of diagnosis, race, grade and time since diagnosis using data from the Surveillance, Epidemiology and End-Results (SEER) program. We identified 116,796 prostate cancer patients diagnosed between 1992 and 1997 and followed them for 20 years. There were 21,896 death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Among the comorbidities that have been found to be particularly relevant is HF, as it has been associated with both an increased risk of cancer and cancer‐related mortality 17 . It is known that PC incidence and mortality increases with age; one study found that the annual probability of PC‐related mortality rises continuously with attained age, from 0.5% at age 50% to 2.0% at age 90 18 . While age has been studied as a significant contributor to higher mortality rates in PC patients, there has been no study that has specifically examined the impact of comorbidities in the context of PC patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Among the comorbidities that have been found to be particularly relevant is HF, as it has been associated with both an increased risk of cancer and cancer‐related mortality 17 . It is known that PC incidence and mortality increases with age; one study found that the annual probability of PC‐related mortality rises continuously with attained age, from 0.5% at age 50% to 2.0% at age 90 18 . While age has been studied as a significant contributor to higher mortality rates in PC patients, there has been no study that has specifically examined the impact of comorbidities in the context of PC patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Age has been associated with survival in many cancer types 38–44 . A recent systematic review of pan‐cancer prognostic clinicopathological factors associated with survival outcomes found that advanced patient age (135 studies) and higher pathological stage (133 studies) were common features associated with death from cancer, including LUAD 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Age has been associated with survival in many cancer types. 38 , 39 , 40 , 41 , 42 , 43 , 44 A recent systematic review of pan‐cancer prognostic clinicopathological factors associated with survival outcomes found that advanced patient age (135 studies) and higher pathological stage (133 studies) were common features associated with death from cancer, including LUAD. 45 Previous studies have shown that aging and cancer are characterized by a series of partially overlapping “hallmarks” including genomic instability, epigenetic alterations, and chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although early-stage low-grade prostate cancer can be cured with surgery or radiation therapy, most patients have progressed to CSPC by the time they are admitted to the hospital. ADT therapy can promote tumor dormancy, prolong the survival of patients, and improve the quality of life, but it can rarely cure prostate cancer, and most tumors will recur [ 110 , 111 ]. Tumor resistance to ADT is cumulative: with the change of lineage, some tumor cells will eventually lose AR expression and develop into small cell carcinoma; this type of tumor is called neuroendocrine prostate cancer (NEPC), and this type of cancer cells express neuroendocrine markers, mostly induced by treatment, and a small part is primary, and does not respond to ARSI et al [ 112 ].…”
Section: Discussionmentioning
confidence: 99%